A miniaturized sensor for detection of formaldehyde fumes. Issue 17 (20th June 2017) - Zilberstein, Gleb; Zilberstein, Roman; Zilberstein, Svetlana; Maor, Uriel; Baskin, Emmanuil; Zhang, Shoumo; Righetti, Pier Giorgio
Abstract: A miniaturized chemical sensor is here described for the analysis of environmental pollutants (VOC: volatile organic chemicals). It is used for remote detection of formaldehyde (FA) fumes in the atmosphere, and is based on the redox reaction between FA and silver nitrate. The sensor is worn as a bracelet and the data acquired are transferred via a Bluetooth channel to a smartphone. A dedicated software transforms the signal from a grey to a color scale. The signal response has been assessed over low (20 to 120 ppb) as well as higher (1–15 ppm range) levels. The sensor has been applied to monitor potential FA fumes of some artwork in the Summer Palace in Beijing and the modifications induced by FA treatment on a precious Stradivarius violin. The performance of this novel sensor is compared with a commercial apparatus widely adopted, namely the Honeywell MultiRAE Lite wireless portable multi‐gas monitor (pumped model).